2019
DOI: 10.31234/osf.io/w87rj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute pain impairs sustained attention

Abstract: Pain affects the lives of many individuals by creating physical, psychological, and economic burdens. A critical psychological factor negatively affected by pain is one’s ability to sustain attention. In order to better understand the effect of pain on sustained attention we conducted three experiments utilizing the psychomotor vigilance task, thought probes, and pupillometry. In Experiment 1, participants in acute pain exhibited overall poorer task performance. However, this effect was localized to the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…At least in theory, we expected some sort of relationship between the rating of pain and the mistakes made in the task. On the one hand, some studies have shown an impairment in the performance of sustained attention tasks in the presence of pain [33][34][35][36][37][38]. This was also to be expected given the nature of the experiment.…”
Section: Plos Onementioning
confidence: 66%
See 2 more Smart Citations
“…At least in theory, we expected some sort of relationship between the rating of pain and the mistakes made in the task. On the one hand, some studies have shown an impairment in the performance of sustained attention tasks in the presence of pain [33][34][35][36][37][38]. This was also to be expected given the nature of the experiment.…”
Section: Plos Onementioning
confidence: 66%
“…The sample of patients with chronic pain we have accessed (n = 49) is relatively small, restricting both the treatment of the data and the statistical analyses that have been conducted. Other researchers that have already studied sustained attention in relation to chronic pain have used samples of a similar size [37][38][39][103][104][105][106][107]. Nevertheless, our view is that a larger sample would have increased the reliability of the results obtained.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we extracted three parameters from the distribution of each individual's RTs: µ, which represents the point of central tendency of the distribution, σ which represents the degree of variability in the distribution, and τ which represents the length of the tail of the distribution. In prior research with the psychomotor vigilance task, motivational incentives have been demonstrated to specifically affect µ, whereas other experiments, like putting participants in acute pain have shown specific effects on τ (Matthew K Robison et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%